COVID-19 AND GLOBAL GENDER GAP: COVID-19 IMPACT ON GENDER İN WORKFORCE (Third Sector Social Economic Review, 2021)
Covid-19 reveals vulnerabilities in social, political and economic systems, and is reflected in gender inequality and manifests itself as a problem in the female workforce.The first condition of offering the best solution to a problem is to be able to measure the problem with its dimensions.In order to solve the gender inequality problem, it is necessary to measure the important determinants.For this purpose, gender gap and workforce reflections in the Covid-19 process were investigated through the Global Gender Index (GGI) indicators.The dimensions of women's economic participation and equal opportunity, educational status, health and survival, and political empowerment were examined.The study is important in terms of defining gender inequalities in a dimension-based and measurable way, since the GGI is a newly known concept in Turkey.The study contributes to the dimensional definition and perspective of the gender inequalities of women in Turkey.Descriptive data analysis shows that the low gender equality in Turkey.
Keywords: Global Gender Gap Index; Gender Inequality; Covid-19; Turkey; Women's Studies